Fare non-repudiation protocol based on identity-based cryptography - LIU Hong-wei; XIE Wei-xin; YU Jian-ping; ZHANG Peng (Tongxin xuebao)
A signature scheme with the one-off blind public key was proposed based on identity-based cryptography,and thus was applied in a new fare non-repudiation protocol.In this protocol,the sender was anonymity,so avoid that the recipient deliberately rejected the files or delayed reading the files when the files were not good for them,which could assure the equity and non-repudiation of the communication between the sender and the recipient.The signature scheme with the one-off blind public key and non-repudiation protocol is both secure and effective by analysis.